BIBLICAL PERFORMANCE CRITICISM UND DAS MARKUSEVANGELIUM - MEISER, Martin (Studia Universitatis Babeș-Bolyai Theologia Catholica Latina, 2022)
Biblical performance criticism and the Gospel of Mark. New Testament texts were mostly not read silently but heard aloud. Accordingly, some of them, especially the Gospel of Mark, still bear the traces of this form of communication and are also calculated to do so. The listeners reacted with emotional statements. The new Biblical Performance Criticism that has emerged in the USA makes these insights the basis of interpretation, in distinction from approaches that are too strongly literary. The present article seeks to raise the profit of this interpretation for textual interpretation and tries to integrate the insights of Biblical Performance Criticism into conventional exegesis of the Gospel of Mark.